Đánh giá hiện trạng và khoanh vùng cảnh báo nguy cơ nứt đất tỉnh Quảng Nam - Hùng, Phạm Văn (Vietnam Journal of Earth Sciences, 2012)
summaryReview of current status and land cracking hazard zoning of the Quang Nam ProvinceQuang Nam Province is located at an active tectonic area. Land cracking hazard occur with increasing scale and cause damage to lives of localresidents. This paper presents the situation and land cracking zoning investigation as a basis for rational use of territory and to prevent disasters.- In the Quang Nam Province there are about 76 land cracking sites in which 15 points caused serious damages and losses such as : Ho Chi Minh route cracking : the A Tep-A Vuong section, Song Bung Pass ; cracked mountains : Dau Voi, Kim Son, Vu ; cracked hills : Cu Lao, Duong Lam ; cracked dam : Tra Can, Phu Loc, Phu Ninh.- The land cracks happened due to fault activities in the context of modern geodynamics. Set of "chicken wing" fractures reflect normal-left slip of the NE-SW faults, normal-right slip of the NW-SE faults, and reversed slip of the sub-latitudinal faults : Bung-Tra Bong River, A Den - Ai Nghia, Phuoc Xuan - Tam Ky, Po Co River, Con River faults,...- The risk of land cracking is very high along affective areas of faults : Song Bung - Tra Bong River, Po Co River, from 5-7 km to 10-15 km width, distributing in the districts of Tay Giang, Nam Giang, Phuoc Son and North Tra My - Nui Thanh. The risk of land cracking is high along fault affected area : Gari - Dac Pree, Tra Don - Tra Mai, Dai Hiep - Thanh My, Hiep Duc - Duy Xuyen, from 2-3 km to 5-7 km in width, in the districts of Phuoc Son, Tay Giang, Dong Giang, Nam Giang, Duy Xuyen, Dai Loc and Phu Ninh. The risk of land cracking is average along fault areas : Za Hung - Dai Lanh, Dai Loc - Nui Thanh, Phuoc Xuan - Tam Ky, Tra Duong- Tam My, from 3 to 5 km in width and distributed in the districts of Tien Phuoc, Hiep Duc, Tien Phuoc, Nui Thanh, Dong Giang, Duy Xuyen. The risk of earth cracking area is low in : A Tep - A Vuong, Que Lam - Duy Phu, Dac Pring River, Zuoih - Cha Val, Ca Dy - Phuoc Hiep and Phuoc Thanh - Tra Nam. Outside faulting areas, land cracking risk are very low